1998
DOI: 10.1093/cercor/8.3.227
|View full text |Cite
|
Sign up to set email alerts
|

A histologically visible representation of the fingers and palm in primate area 3b and its immutability following long-term deafferentations

Abstract: An isomorph of the glabrous hand is visible in primary somato-sensory cortex (area 3b) of owl monkeys in brain sections cut parallel to the surface and stained for myelin. A mediolateral row of five ovals, separated by myelin-light septa, represents digits and corresponds precisely with cortical sites activated by light touch on individual digits in microelectrode recordings. A number of caudal ovals relate to pads of the palm. A more distinct septum separates the hand from the more lateral face representation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(138 citation statements)
references
References 56 publications
10
124
4
Order By: Relevance
“…Additionally, within 3b, the border between the hand and facial representation (hand/face septum) was clearly identifiable. As reported by other investigators (Jain et al, 1998), we found close correspondence between physiologically and histochemically identified borders (Fig. 4 A).…”
Section: Neurophysiological Mapping Resultssupporting
confidence: 91%
“…Additionally, within 3b, the border between the hand and facial representation (hand/face septum) was clearly identifiable. As reported by other investigators (Jain et al, 1998), we found close correspondence between physiologically and histochemically identified borders (Fig. 4 A).…”
Section: Neurophysiological Mapping Resultssupporting
confidence: 91%
“…Less noticeable septa separate representations of other body parts in the part of 3b devoted to the body as well. Most notably, thin septa separate territories for the representation of each digit of the hand in cortex just medial to the hand-face junction (Jain et al, 1998). These isolating septa are also apparent in area 3b of macaque monkeys, where they can be identified as early as 2 weeks after birth .…”
Section: Representation Of Tongue and Teeth In Area 3b And Adjoining mentioning
confidence: 89%
“…In owl monkeys and squirrel monkeys, myelin-rich isomorphs associated with the oral structures and digits vary in size (Fig. 5 D and E) (45,46), as do the digit isomorphs for the digits in macaque monkeys, particularly D1 (27). Ocular dominance columns in V1 of squirrel monkeys can show extreme variability (47).…”
Section: Within-species Variabilitymentioning
confidence: 95%